Adaptation of the Impulsive Sensation Seeking Scale to Turkish - (:unkn) unknown (TURKISH GREEN CRESCENT SOC, 2021)
The aim of this study was to examine the validity and reliability of the Impulsive Sensation Seeking Scale (ImpSS) for the Turkish sample. A total of 459 individuals (221 female and 238 males, mean age = 34.94 +/- 10.52years) voluntarily participated in this study. The ImpSS, developed by Zuckerman et al. (1993), measures the sensation-seeking traits of individuals. It includes two subdomains, Impulsivity and Sensation Seeking, and 19 items. The exploratory factor analysis revealed that the 19 items were in a two-factor structure, and this result was also confirmed by confirmatory factor analysis. Cronbach's alpha for reliability of the Impulsivity and Sensation Seeking subscales, and the full scale, was 0.77, 0.78, and 0.84; 0.75, 0.73, and 0.80 in Kuder-Richardson formula (KR-21); and 0.75, 0.79, and 0.82 in test-retest, respectively. The Turkish version of the ImpSS is valid and reliable for measuring general sensation seeking.
Keywords: Impulsive sensation seeking; impulsivity; reliability; sensation seeking; validity; KUHLMAN PERSONALITY QUESTIONNAIRE; PSYCHOMETRIC PROPERTIES; SUBSTANCE USE; VALIDITY; VERSION; ZKPQ